Mixed High-Grade Neuroendocrine Carcinoma with Villous Adenoma in the Duodenum: A First Case Report - Ali, MD, Mahmoud; Kahaleh, MD, Michel; Zhou, MD, PhD*, Zhongren (North American Journal of Medicine and Science, 2021)
Mixed neuroendocrine non-neuroendocrine neoplasm (MiNEN) represents a rare diagnosis in the gastrointestinal tract. Only a few cases of MiNEN occurring in the small bowel had been previously reported. Here we report the first case of mixed high grade neuroendocrine carcinoma with villous adenoma arising in the duodenum. The patient is an 87-year-old female who presented for management of a 3.4 cm polypoid-like duodenal mass that was noted on a prior abdominal CT scan. PET scan showed intense uptake within the second portion of the duodenum consistent with a neoplasm. A biopsy previously performed showed tubulovillous adenoma. The patient had a remote history of breast cancer. Esophagogastroduodenoscopy was performed which showed fungating mass occupying 50% of the duodenal lumen and polypectomy was done. Grossly, the duodenal mass appeared as a pink-tan polypoid fragment of tissue. Microscopically, a villous adenoma is seen with focal area of high-grade dysplasia. Admixed with the villous adenoma, there are sheets of homogeneous small cells with high nuclear-cytoplasmic ratio, nuclear molding, high mitotic activity, and finely granular chromatin which stained positive for synaptophysin, CD56, CAM5.2, and CK8/18 while stained negative for chromogranin A, CK7, CK20, and CDX2. These findings support the diagnosis of high-grade neuroendocrine carcinoma arising in a background of villous adenoma. We report a first case of mixed high grade neuroendocrine carcinoma with villous adenoma arising from the duodenum. [N A J Med Sci. 2021;1(1):004-007. DOI: 10.7156/najms.2021.1401004]